Improving Students’ Learning Outcomes in Mathematics through the Use of the Team Games Tournament (TGT) Method in Class XI A3 of SMA Negeri 3 Palu - Zubaer, Rizky Ramadhani; Murdiana, I Nyoman; Naim, Siti Hanifah (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Mathematics is often perceived as difficult by students due to its association with formulas and abstract concepts, leading to low motivation and learning outcomes. This condition was observed in class XI A3 of SMA Negeri 3 Palu, where most students had not yet achieved the Minimum Mastery Criteria (KKM) in statistics. This study aims to improve mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model combined with the Team Games Tournament (TGT) method. The research employed Classroom Action Research (CAR) involving 36 students of class XI A3, with data collected through tests, observation, and documentation. The findings revealed an improvement in average learning outcomes from 68.1% in the pre-cycle to 76.5% in cycle I, and 92.5% in cycle II. Learning mastery also increased from 33.3% in the pre-cycle to 69.4% in cycle I, and reached 88.8% in cycle II. Therefore, the implementation of PBL integrated with TGT proved effective in enhancing conceptual understanding, learner independence, and mathematics achievement.